Pengembangan Pemahaman Kegiatan Nurmerasi Terhadap Siswa-Siswi di SMP Negeri Satu Atap 3 Pubian, Lampung Tengah - Annisa Nurhayati Annisa Nurhayati; Elfahmi Lubis; Septina Lisdayanti; Wellyana Wellyana (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The Teaching Campus Program launched by the Ministry of Education and Culture of the Republic of Indonesia, is a solution to accelerate education during the COVID-19 pandemic. The Campus Teaching Program involves all students in Indonesia whose objectives can be: Instilling a sense of empathy and social belonging, Sharpening thinking skills in working together across fields of knowledge and various student origins, insight, character and soft skills of students, Can improve the order of education in schools, Upgrade administration and technology. lack of understanding of students in remembering and memorizing makes a lack of interest in learning numeracy in students. The purpose of implementing the Teaching Campus program is to empower students to assist the teaching process in junior high schools around the village/city where they live. The purpose of this nursery activity is to take a gradual approach making changes to students is not easy, the dedication there as a student to change children who don't like learning to be diligent in learning numeracy activities to remember, understand and practice Community service to students is carried out directly outside of class hours or during math subjects, this activity is a mandatory activity for students to change students' mindsets.